COVID-19, SECURITIZATION, AND TERRORISM: NATIONAL SECURITY CHANGE MANAGEMENT DILEMMA - Helda Risman; Pujo Widodo; Resmanto Widodo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
The Corona Virus Disease 2019 (Covid-19) pandemic is spreading globally, including in Indonesia, with a significant impact not only in limited a sphere of the threat to public health. The Covid-19 pandemic shaped social phenomenon followed by the changes in the social order of life into the securitization process with multi-dimensional impacts. Due to restrictions extensively, society's liability realities become an opening fissure for terrorist groups to persist in their actions. This rational context raises awareness for the State as State-actor in the security realm to generate security for its people. This paper aims to analyze how the expansion of the Covid-19 outbreak with multi-dimensional impacts in the securitization approach, counting terrorism expansion, and how the State dealing with as a State-actor. Using a qualitative approach, the authors expound on national security and change management theory, illustrating how the Government is a state-actor within its strategy. In responding to the emerging constellation, there are various dynamic challenges for the Government, within its central powers and regional authorities, toward change management dilemmas in the context of national security. At the end of the discussion, it portrays the urgency of responding to the strategic changes in the framework of change management under the top leader's forceful strategic leaderships in integrating all components of the nation.